1985
DOI: 10.1523/jneurosci.05-06-01591.1985
|View full text |Cite
|
Sign up to set email alerts
|

Response characteristics of mammalian cochlear hair cells

Abstract: Intracellular recordings were made from the low frequency region (third turn) of the guinea pig cochlea. Response characteristics are compared to gross potentials obtained from the organ of Corti fluid space. Inner hair cells (IHCs) possess relatively low (median, -32 mV) initial membrane potentials, whereas that of outer hair cells (OHCs) is higher (median, -53.5 mV). In response to tone burst stimuli, both cell types produce a combination of AC and DC responses. The latter are depolarizing for IHCs but may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
132
0
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(153 citation statements)
references
References 65 publications
19
132
0
2
Order By: Relevance
“…In mammals, the stimulus-driven component of the firing rate seems to be proportional to sound pressure squared, corresponding to sound intensity (Yates 1990;Yates et al 1990). The same type of growth was found in the DC response of inner hair cells (Dallos 1985). A recent modeling study suggests that the effect is related to the nonlinear gating of the transducer current (Lopez-Poveda and Eustaquio-Martin 2006).…”
Section: Introductionsupporting
confidence: 59%
“…In mammals, the stimulus-driven component of the firing rate seems to be proportional to sound pressure squared, corresponding to sound intensity (Yates 1990;Yates et al 1990). The same type of growth was found in the DC response of inner hair cells (Dallos 1985). A recent modeling study suggests that the effect is related to the nonlinear gating of the transducer current (Lopez-Poveda and Eustaquio-Martin 2006).…”
Section: Introductionsupporting
confidence: 59%
“…Recordings from saccular afferent fibers in bullfrogs, white-lipped frogs, and the northern leopard frog (R. pipiens) have shown that weak seismic and auditory stimuli evoke maximum spike rates for frequencies near 50 Hz (13,14,37,38), and that the low-frequency roll-off can be due to the phaselocked firing of a single spike in the postsynaptic cell per stimulus cycle (13,14). The sinusoidal stimuli used here (Ϯ5 mV centered at Ϫ60 mV), were small compared with the stimuli used in most voltage-clamp studies but were larger than the V m oscillations expected to occur at sensory threshold (15). In both whole-cell and perforated-patch experiments, the exocytic rate during 1 s of 50-Hz stimulation was two to three times the rate for 5-or 200-Hz stimulation, but, when expressed as vesicles per stimulus cycle, the rate was greatest at 5 Hz (5.1 SV per cycle, compared with 1.9 SV per cycle at 50 Hz and 0.14 SV per cycle at 200 Hz) (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Green and purple dashed lines indicate estimated numbers of docked SVs and docked plus undocked SVs, respectively, that are associated with synaptic ribbons. vivo (15). Continuous depolarization for 30 ms (stimulus A) evoked a ⌬C m of 14 Ϯ 3 fF, whereas two 10-ms depolarizations separated by 10 ms of hyperpolarization (stimulus B) delivered to the same 19 cells evoked a significantly larger ⌬C m of 25 Ϯ 4 fF (P ϭ 0.018), although stimulus A caused more total Ca 2ϩ influx than stimulus B (Fig.…”
Section: The Pool Of Docked Svs Accounts For the Fastest Exocytic Commentioning
confidence: 89%
“…At least at the base of the cochlea, the tuning of ANFs (Narayan et al 1998;Ruggero et al 2000;Temchin et al 2008b) and IHC tuning curves (Kössl and Russell 1992;Sellick et al 1983) reflect BM tuning. Furthermore, there is no evidence disputing the conclusion that, at the apex of the cochlea, the frequency tuning of IHCs (Dallos 1985(Dallos , 1986) "results more from the micromechanical properties of the cochlea than from intrinsic properties of the cells themselves" (Kros 1996). Therefore, it is likely that the CF-specific nonlinearities illustrated in Figures 2 and 5 are present at the input to the stereocilia of apical IHCs and that their antecedents in organ of Corti vibrations in chinchilla were not detected because of abnormalities due to surgical damage (such as puncturing of Reissner's membrane; Dong and Cooper 2006).…”
Section: Anf Phase-frequency Curvesmentioning
confidence: 99%